Impact of decentralized management on sickness absence in hospitals: a two-wave cohort study of frontline managers in Danish hospital wards - Thim Prætorius; Thomas Clausen; Ann Dyreborg Larsen; Jonas Kirchheiner Rasmussen; Lykke Margot Ricard; Peter Hasle (BMC, 2024)
Abstract Background This study explores the impact of decentralized management on the sickness absence among healthcare professionals. Sickness absence is a reliable indicator of employees' wellbeing and it is linked to management quality. However, the influence of decentralized management on sickness absence has not been adequately studied. Methods The research design combined a two-wave, web-survey of frontline managers in two Danish university hospitals with administrative data on sickness absence at the ward-level. The first and second wave included data from 163165 and 137 frontline managers linked to 121 wards and 108 wards. Data was analysed using an ordinal logistic regression model. Results Wards where frontline managers had the highest level of decentralised decision authority compared to none showed lower odds of ward-level sickness absence (ORcrude: 0.20, 95% CI: 0.05-0.87). A very high extent of cross-functional decision authority showed lower odds of sickness absence (ORcrude: 0.08, 95% CI: 0.01-0.49). Overall, the results showed a clear data trend, although not all results were statistically significant. Conclusion Higher levels of decentralized management in wards were positively associated with lower risks of sickness absence in hospital wards. The study supports future research on how to empower decision autonomy at the frontline level of management.